Non-Bijective Translations on the Triangular Plane - Abuhmaidan, Khaled; Nagy, Benedek (IEEE, 2018)
In discrete and digital geometry, rotations with the composition of translations have been measured and examined carefully on the square and the hexagonal grids. The translation has never been considered individually because it obviously leads to the isometric translation on these grids. However, the triangular grid is not a point lattice, thus, it is worth to consider the translation itself. In this article, translations on the triangular grid are investigated and the vectors of bijective and non-bijective translations are specified.
IEEE 16th World Symposium on Applied Machine Intelligence and Informatics (SAMI) Dedicated to the Memory of Pioneer of Robotics Antal (Tony) K. Bejczy -- FEB 07-10, 2018 -- Kosice, SLOVAKIA
Keywords: non-traditional grids; triangular grid; transformations; image processing; computer graphics; discretized translations; digital geometry